The U.S. fracking boom: Impact on oil prices - Manuel Frondel; Marco Horvath (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
As of late 2008, the steady decline of U.S. crude oil production over the last decades was reversed by the increased adoption of the hydraulic fracturing ("fracking") technology. Adapting the supply-side model proposed by Kaufmann et al. (2004) to assess OPEC's ability to influence real oil prices, this paper investigates the effect of the increase in U.S. oil production due to fracking on world oil prices. Among our key results obtained from (dynamic) OLS estimations, there is a statistically significant negative long-run relationship between increased U.S. oil production and oil prices. – – Mit Ende des Jahres 2008 endete der Jahrzehnte währende stetige Rückgang der U. S. Rohölproduktion aufgrund des stark steigenden Einsatzes der Fracking genannten Technologie zur Förderung von Öl und Gas aus Schiefergestein. Durch Anpassung des Angebotsmodells von Kaufmann, Dees, Karadeloglou und Sanchez (2004), mit dem die Möglichkeit der OPEC zur Beeinflussung des Rohölpreises analysiert wurde, untersucht dieser Artikel den Effekt des Anstiegs der U.S. Rohölproduktion infolge von Fracking auf die globalen Rohölpreise. Als wesentliches Resultat unserer dynamischen OLS-Schätzungen ergibt sich eine statistisch signifikant negative Langfristbeziehung zwischen der seit 2008 massiv gestiegenen U.S. Rohölförderung und den weltweiten Ölpreisen.
Keywords: Q41; Q32; L71; 330; dynamic OLS; error correction model; shale oil